The Effect of Guided Discovery Learning Model on Students' Mathematical Communication Skills - Hesti Nurohmah; Rini Asnawati; Santy Setiawati (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study aims to determine the effect of Guided Discovery Learning model on students' mathematical communication skills. The population in this study consists of all seventh-grade students of SMP Negeri 35 Bandar Lampung in the 2025/2026 academic year totaling 87 students distributed across three classes. The sample in this study includes class VII.3 as the experimental class with 29 students and class VII.2 as the control class with 29 students selected using cluster random sampling technique. The type of research used is quasi experimental research. The design used is the pretest-posttest control group design. The data in this study is quantitative data obtained through a mathematical communication skills test. Based on the result of hypothesis test using t-test, it was found that the average gain score of mathematical communication skills for students who participated in Guided Discovery Learning model was 0.69, which was higher than the average gain score of 0.35 achieved by students who participated in conventional learning. It can be concluded that the implementation of Guided Discovery Learning model has an effect on students' mathematical communication skills.